Analysis and optimization of threaded shear energy absorbing components of collision resistance hydraulic support columns - Zuen Shang; Jiyang Meng; Qian Liu; Peng Yang; Xisheng Yu (Scientific Reports)
Abstract Conventional energy-absorbing components have limitations in terms of performance and functionality, including significant variability in reaction forces, inherent instability, and inadequate energy absorption capabilities. This paper presents a threaded shear-type energy-absorbing component designed for anti-impact hydraulic support columns, specifically for ZQL advancing support roadway hydraulic supports. The component operates based on the principle of threaded shear energy absorption. Its key structural parameters—such as thread shape, outer diameter, and pitch—are optimized using single-factor and response surface experimental design methods. Shear simulations are performed to analyze the deformation and force-displacement characteristics across various structural configurations. The impact of different thread parameters on energy absorption performance is evaluated, with quasistatic shear tests and simulations validating the results. The optimized design enhances energy absorption efficiency and provides a foundation for future research on integrating these components into hydraulic support systems to improve overall performance.